1 ' S-1 '-acetoxyeugenol acetate: a novel phenylpropanoid from Alpinia conchigera enhances the apoptotic effects of paclitaxel in MCF-7 cells through NF-kappa B inactivation - In, L.L.A.; Azmi, M.N.; Ibrahim, H.; Awang, K.; Nagoor, N.H. (2011)
In this study, the apoptotic mechanism and combinatorial chemotherapeutic effects of the cytotoxic phenylpropanoid compound 1'S-1'-acetoxyeugenol acetate (AEA), extracted from rhizomes of the Malaysian ethnomedicinal plant Alpinia conchigera Griff. (Zingiberaceae), on MCF-7 human breast cancer cells were investigated for the first time. Data from cytotoxic and apoptotic assays such as live and dead and poly-(ADP-ribose) polymerase cleavage assays indicated that AEA was able to induce apoptosis in MCF-7 cells, but not in normal human mammary epithelial cells. A microarray global gene expression analysis of MCF-7 cells, treated with AEA, suggested that the induction of tumor cell death through apoptosis was modulated through dysregulation of the nuclear factor-kappaB (NF-kappa B) pathway, as shown by the reduced expression of various kappa B-regulated gene targets. Consequent to this, western blot analysis of proteins corresponding to the NF-kappa B pathway indicated that AEA inhibited phosphorylation levels of the inhibitor of kappa B-kinase complex, resulting in the elimination of apoptotic resistance originating from NF-kappa B activation. This AEA-based apoptotic modulation was elucidated for the first time in this study, and gave rise to the proposal of an NF-kappa B model termed the 'Switching/Alternating Model.' In addition to this, AEA was also found to synergistically enhance the proapoptotic effects of paclitaxel, when used in combination with MCF-7 cells, presumably by a chemosensitizing role. Therefore, it was concluded that AEA isolated from the Malaysian tropical ginger (A. conchigera) served as a very promising candidate for further in-vivo development in animal models and in subsequent clinical trials involving patients with breast-related malignancies. Anti-Cancer Drugs 22:424-434 (C) 2011 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.